A Major Role of the RecFOR Pathway in DNA Double-Strand-Break Repair through ESDSA in Deinococcus radiodurans - Bentchikou, Esma (Public Library of Science, 2010)

(untitled)
In Deinococcus radiodurans, the extreme resistance to DNA–shattering treatments such as ionizing radiation or desiccation is correlated with its ability to reconstruct a functional genome from hundreds of chromosomal fragments. The rapid reconstitution of an intact genome is thought to occur through an extended synthesis-dependent strand annealing process (ESDSA) followed by DNA recombination. Here, we investigated the role of key components of the RecF pathway in ESDSA in this organism naturally devoid of RecB and RecC proteins. We demonstrate that inactivation of RecJ exonuclease results in cell lethality, indicating that this protein plays a key role in genome maintenance. Cells devoid of RecF, RecO, or RecR proteins also display greatly impaired growth and an important lethal sectoring as bacteria devoid of RecA protein. Other aspects of the phenotype of recFOR knock-out mutants paralleled that of a ΔrecA mutant: ΔrecFOR mutants are extremely radiosensitive and show a slow assembly of radiation-induced chromosomal fragments, not accompanied by DNA synthesis, and reduced DNA degradation. Cells devoid of RecQ, the major helicase implicated in repair through the RecF pathway in E. coli, are resistant to γ-irradiation and have a wild-type DNA repair capacity as also shown for cells devoid of the RecD helicase; in contrast, ΔuvrD mutants show a markedly decreased radioresistance, an increased latent period in the kinetics of DNA double-strand-break repair, and a slow rate of fragment assembly correlated with a slow rate of DNA synthesis. Combining RecQ or RecD deficiency with UvrD deficiency did not significantly accentuate the phenotype of ΔuvrD mutants. In conclusion, RecFOR proteins are essential for DNA double-strand-break repair through ESDSA whereas RecJ protein is essential for cell viability and UvrD helicase might be involved in the processing of double stranded DNA ends and/or in the DNA synthesis step of ESDSA.